A arte de intervir no espaço urbano: educação do sensível e educação política de jovens em Novo Hamburgo - RS - Longoni, Daniela da Rosa (Universidade do Vale do Rio do Sinos, 2009)
Taking into account the importance of the (re)vision of formative processes related to different kind of youth and the importance of political education and sensitive education in this context, this study analysed the contributions of a urban intervention expressive experience, built within a formative process in art, on the political education of young people in Novo Hamburgo-RS. By way of a formative-intervention design, this research generated a formative experience at the interface of political education and art education, analyzing the problematization process of sociopolitical concepts shared by young people throughout the process. The research demonstrated that the juveniles problematizations were mediated by the expressive production that stresses daily life thinking, by the collective decision making process on the collective expressive production; by the influence of the context on the development of the workshop; by the image reading that stimulates daily life thinking; by the gathering and interpr
Keywords: educação política; ensino da arte; intervenção urbana; educação de jovens; art education; political education; urban intervention; education of youth; Ciências Humanas